Ultrastructure of venous wall before and after the treatment with sclerosant - Segeda, T.P.; Khodos, V.A.; Zaritskaya, V.I. (Pathologia, 2013)
Basing upon results of ultrastructure studies of surgical specimens obtained from venous vessels after the use of sclerosant, it has been found out that the intensity of damage rises according to medicine concentrations increase (2%, 3%, 5% respectively), and 3% concentration is optimal for the purposes of surgical fibrosclerosis.